A venda pomerana no Espírito Santo: lugar sociopolítico, econômico e identitário (1857 - 2021) - Manske, Cione Marta Raasch (2021)
The present thesis addresses the relationship of the Pomeranians and their descendants with general stores in Santa Maria de Jetibá, state of Espírito Santo (Brasil). The object of the analysis are the general stores as places of sociability, economy, power and ethnic and identity recognition of these immigrants and their descendants. The thesis of the research understands that the ethnic identity, brought by immigrants from Pomerania, during the movement to the state of Espírito Santo back in the XIX century and in the settlement in Santa Maria de Jetibá, remains woven in the memory and in the daily of general stores to the contemporaneity. The social-cultural relations, the economy and the power negotiations between the members of this group are part of this conviviality. The current use of German, Pomeranian and Portuguese languages was present as a factor of support and aggregation of the salesmen with the immigrants and their descendants continuously throughout the process of structuration of the organization and of the Pomeranian immigrants and descendants in the territory of Santa Maria de Jetibá. The sellers, given the socio-political and economic power they had over immigrants and descendants, lived in conflicting relations with the Lutheran pastors. These have always been active participants in the integration of the group and symbols of the maintenance of religious values carried in the chests of the Atlantic crossing. The Lutheran pastors, leaders of the church to which the majority of the Pomeranians were affiliated, at the same time, reached repercussion in the disputes with the sellers for socioeconomic and political power. The analysis of this constitution is based on the documentary body of the research through written sources, bibliographies, and other oral sources. It concludes that memory, identity and ethnicity embody the place of sales in the life stories and trajectories of the Pomeranians and descendants in Santa Maria de Jetibá.